The Role of Acute Phase Reactants (Fibrinogen, Ferritin, Albumin, Calcium) in Pregnant Women with Preterm Delivery - w. Ibrahim, wasan; T. Mosa, Maha (Journal of the Faculty of Medicine Baghdad, 2022)
Background: Preterm labor and related prematurity are predisposing factors that increase perinatal morbidity and mortality. Acute phase reactants are inflammatory markers which are positive and negative reactants explained by the reaction of reactants to the subclinical infection that are commonly associated with preterm labor.Objectives: To assess the role of acute phase reactants in pregnant women with preterm delivery.Patients and method: A case control study conducted in Gynecological Department of Baghdad Teaching Hospital from 1st February 2021 to 30th October 2021, on one hundred pregnant women with gestational age (28weeks - 36weeks+6days) who attended outpatient clinic; fifty pregnant women with established preterm labor as case group and fifty pregnant women with no signs and symptoms of preterm labor as control group. Data was collected using structured questionnaire included demographic features, and biochemical parameters (serum ferritin (ng/ml), albumin (gm/dl), fibrinogen (mg/dl), and calcium (mg/dl) .Results: Mean±SD serum ferritin in control group was (46.2 ± 16.2 ng/ml) while in case group (52.47 ± 11.6ng/ml) with significant difference between both groups (P=0.03), mean±SD serum albumin in control group (3.18 ± 0.31 ng/ml) while in case group (2.92 ± 0.39) with highly significant difference between both groups (P